Labor markets in an era of adjustment - Horton, Susan; Kanbur, Ravi; Mazumdar, Dipak (Washington, D.C. : World Bank, 1994)
This book consists of two volumes resulting from a large research project undertaken by the Economic Development Institute of the World Bank.
Includes bibliographical references.
osc 16/01/14
Loans
Keywords: Structural adjustment (Economic policy) -- Developing countries -- Congresses; Labor market -- Developing countries -- Case studies -- Congresses; Structural adjustment (Economic policy) -- Developing countries -- Case studies -- Congresses